Criminal Responsibility of Perpetrators of Narcotics Trafficking by Children - Hafiy Ghafara Rahman; Bambang Sukoco (Proceeding International Conference Restructuring and Transforming Law, 2023)
The purpose of this study is to analyze whether children are ensnared by criminal crimes, who are devoted to children as drug traffickers. Child rights governed under laws are optimally implemented by national narcotics agencies when dealing with child trafficking. This research uses a normative approach with the use of descriptive‐analytical secondary data. The child should also have the same due due as an adult. Each child even has certain rights when a child is dealing with the law. As a result of this study, BNN will continue to seek to fulfill the rights of every child governed under the laws of law.